Analysis on propagation characteristics of voltage sag through different types of transformers. Issue 1 (January 2021) - Jiang, Jiandong; Gao, Ang
Abstract: Transformer is a key factor that can not be ignored in the process of voltage sag propagation. In this paper, the transmission characteristics of voltage sag caused by different types of short circuit are analyzed through the different transfer matrix of transformer with different connection methods, including amplitude change, waveform distortion and phase jump. The distribution network model is established by PSCAD, and the propagation characteristics are verified. The conclusion has certain significance for judging the type of voltage sag from the load side, evaluating the degree of voltage sag, and selecting the treatment measures of voltage sag.